The EBLM project X. Benchmark masses, radii, and temperatures for two fully convective M-dwarfs using K2. Issue 4 (24th February 2023) - Duck, Alison; Martin, David V; Gill, Sam; Armitage, Tayt; Rodríguez Martínez, Romy; Maxted, Pierre F L; Sebastian, Daniel; Sethi, Ritika; Swayne, Matthew I; Cameron, Andrew Collier; Dransfield, Georgina; Gaudi, B Scott; et al.
ABSTRACT: M-dwarfs are the most abundant stars in the galaxy and popular targets for exoplanet searches. However, their intrinsic faintness and complex spectra inhibit precise characterization. We only know of dozens of M-dwarfs with fundamental parameters of mass, radius, and effective temperature characterized to better than a few per cent. Eclipsing binaries remain the most robust means of stellar characterization. Here we present two targets from the Eclipsing Binary Low Mass (EBLM) survey that were observed with K2: EBLM J0055-00 and EBLM J2217-04. Combined with HARPS and CORALIE spectroscopy, we measure M-dwarf masses with precisions better than 5 per cent, radii better than 3 per cent, and effective temperatures on order 1 per cent. However, our fits require invoking a model to derive parameters for the primary star and fitting the M-dwarf using the transit and radial velocity observations. By investigating three popular stellar models, we determine that the model uncertainty in the primary star is of similar magnitude to the statistical uncertainty in the model fits of the secondary M-dwarf. Therefore, whilst these can be considered benchmark M-dwarfs, we caution the community to consider model uncertainty when pushing the limits of precise stellar characterization.